Correlation of Dyslipidemia and Inflammation With Obstructive Sleep Apnea Severity - Popadic, Viseslav; Brajkovic, Milica; Klasnja, Slobodan; Milic, Natasa; Rajovic, Nina; Lisulov, Danica Popovic; Divac, Anica; Ivankovic, Tatjana; Manojlovic, Andrea; Nikolic, Novica; Memon, Lidija; Brankovic, Marija; et al. (Frontiers in Pharmacology, 2022)
Introduction: Obstructive sleep apnea (OSA) is a serious condition linked with various metabolic disorders and associated with increased all-cause and cardiovascular mortality. Although the potential mechanisms of pathophysiological processes related to OSA are relatively well known, the data regarding the correlation between obstructive sleep apnea, dyslipidemia, and systemic inflammation are still inconclusive. Methods: The study was conducted as a retrospective cohort study including 332 patients with newly diagnosed obstructive sleep apnea during the period between April 2018, and May 2020, in University Clinical Hospital Center “Bezanijska kosa”, Belgrade, Serbia. Polysomnography was performed in all patients according to the protocol. Numerous demographic, antropometric, laboratory, and clinical data were correlated to Apnea-Hypopnea Index (AHI) as a dependent variable, with a particular review on the relation between lipid abnormalities, inflammatory parameters, and obstructive sleep apnea severity. Multivariate logistic regression model was used to assess predictors of severe OSA (AHI ≥30 per hour). Results: A total of 328 patients were included in the study. The mean age of the patients was 54.0±12.5 years and more than two-thirds were male (68.8%). The majority of the patients had an AHI of at least 30 events per hour. Patients with severe OSA were more frequently male, obese, hypertensive and hyperlipidemic, and had increased neck circumference (both male and female patients). One hundred and thirty-two patients had metabolic syndrome. Patients with severe OSA more frequently had metabolic syndrome and significantly higher levels of glucose, creatinine, uric acid, AST, ALT, CK, microalbumine/ creatinine ratio, triglyceride, total cholesterol, HDL, total cholеsterol to HDL‐C ratio, CRP, and ESR. In the multivariate linear regression model with AHI (≥30 per hour) as a dependent variable, of demographic and clinical data, triglycerides ≥1.7 mmol/l and CRP >5 mg/L were significantly associated with AHI≥30 per hour. Conclusion: The present study on 328 patients with newly diagnosed obstructive sleep apnea revealed significant relation of lipid abnormalities, inflammatory markers, and other clinically important data with obstructive sleep apnea severity. These results can lead to a better understanding of the underlying pathophysiological processes and open the door to a new world of potentially useful therapeutic modalities.